2013
DOI: 10.2147/ijn.s39048
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cellular uptake and toxicity of aminosilane-coated iron oxide nanoparticles with different charges in central nervous system-relevant cell culture models

Abstract: Background: Aminosilane-coated iron oxide nanoparticles (AmS-IONPs) have been widely used in constructing complex and multifunctional drug delivery systems. However, the biocompatibility and uptake characteristics of AmS-IONPs in central nervous system (CNS)-relevant cells are unknown. The purpose of this study was to determine the effect of surface charge and magnetic field on toxicity and uptake of AmS-IONPs in CNS-relevant cell types. Methods: The toxicity and uptake profile of positively charged AmS-IONPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 38 publications
5
73
0
Order By: Relevance
“…ML-MM is a chemically-defined, serum-free preparation. Particle characterization measurements of bare nanoparticles are commonly conducted in PBS/deionized water [44,45], but cannot address alterations in particle properties that occur in complex biological growth media, which are of higher predictive value for the in vivo situation.…”
Section: Resultsmentioning
confidence: 99%
“…ML-MM is a chemically-defined, serum-free preparation. Particle characterization measurements of bare nanoparticles are commonly conducted in PBS/deionized water [44,45], but cannot address alterations in particle properties that occur in complex biological growth media, which are of higher predictive value for the in vivo situation.…”
Section: Resultsmentioning
confidence: 99%
“…35 In endothelial cells, treatment with up to 100 μg Fe /mL SPIONs was well tolerated, although cellular uptake was not determined in that study. 36 During clinical applications like magnetic resonance imaging or magnetic hyperthermia, SPIONs come into direct contact with endothelial cells when administered into veins or arteries. We therefore investigated SPION accumulation/ uptake in endothelial cells, which are the first contact cells for all nanoparticles intended for intravascular administration.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, to obtain a better understanding of the influence of nanoparticles on cells, it is crucial to gather all relevant concentration parameters, such as μg Fe /mL media, μg Fe /cm 2 plate surface, and pg Fe /cell and, above all, the respective cell number of the measured sample. The methods applied in our study aimed at quantification of cell numbers in parallel with the measurement of SPION content, in order to correlate the cellular effects with the average amount of SPIONs per cell.…”
mentioning
confidence: 99%
“…On the other hand, Marcu et al 16 targeted a MCF-17 breast cancer cell line delivering iron oxide nanoparticles loaded with Violamycine B1, an anthracycline antibiotic that enhanced cellular uptake activity and cell death. Sun et al 17 showed that toxicity depends more strongly on the surface coating than the amount of iron oxide present in the cell. Also, SPIOs coated with amino or carboxylate groups were shown to be nontoxic against a mouse brain microvessel endothelial cell line (bEnd.3) and primary culture of mouse astrocytes and neurons, at concentrations below 100 µg/mL.…”
mentioning
confidence: 99%